Pemanfaatan Penggunaan Chat GPT Dalam Meningkatkan Kemampuan Pengajaran Bahasa Inggris - Chairunnisa, Nazli Fahada, Jonris Tampubolon, (Center of Knowledge : Jurnal Pendidikan Dan Pengabdian Masyarakat, 2023)
ChatGPT is an AI tool that has sparked debates about its potential implications for education. We used the SWOT analysis framework to outline ChatGPT’s strengths and weaknesses and to discuss its opportunities for and threats to education. ChatGPT can increase access to information, facilitate Personalised and complex learning, and decrease teaching workload, thereby making key processes and tasks more efficient. The weaknesses are a lack of deep understanding, difficulty in evaluating the quality of responses, a risk of bias and discrimination, and a lack of higher-order thinking skills. The aim of this community service is to inform about the benefits of using ChatGPT in teaching English for teachers at Mts Muhammadiyah 15 Medan and to conduct a SWOT analysis of ChatGPT.